CIVIL LIABILITY FOR MEDICAL ERROR IN AESTHETIC DAMAGE (CIPEEX, 2022)
THIS CHAPTER AIMS TO ANALYZE CIVIL LIABILITY FOR AESTHETIC DAMAGE CAUSED BY A MEDICAL ERROR COMMITTED IN AN AESTHETIC SURGERY PROCEDURE. IT SEEKS TO PRESENT THE MAIN ASPECTS AND CHARACTERISTICS ABOUT THE CIVIL LIABILITY INSTITUTE, IT ALSO ADDRESSES ISSUES ABOUT THE LEGISLATION ON CIVIL LIABILITY, AS WELL AS SOME CONSIDERATIONS ABOUT THE DUTY OF REPARATION. PRESENTATION OF CONCEPTS AND LEGAL FORMS AND JURISPRUDENCE.
Keywords: Keywords: analyze civil; medical error; reparation